The Analysis of Plot in â€œSnow White and the Seven Dwarfsâ€ Story by Vera Southgate and Disney â€œSnow White and the Seven Dwarfsâ€ by Using Formalism Approach - Luh Rista Hardiantini (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aims to analyze the intrinsic element: it is the plot in the story